Statistic Fluida Teaching Module Oriented to STEM-PjBL for Improving Learners' Creativity - Octapera, Lia Arilla; Suyidno, Suyidno; Mahtari, Saiyidah (Universitas Lambung Mangkurat, 2024)
Creativity is a main concern in the 21st-century curriculum, but this is rarely implemented in the physics learning process in schools. This research aims to produce a STEM-PjBL-oriented static fluid teaching module worthy of its validity and practicality. This research is development research using the ADDIE model. The research trial subjects were 32 students in class XI 1 SMA consisting of 16 men and 16 women. Data was obtained through module validation sheets and teaching module implementation sheets. The data analysis technique is descriptive, qualitative, and quantitative. The expert and practitioner validation results obtained validity and reliability values for the teaching module of 3.46 and 0.60 with very valid and reliable categories. Apart from that, the results of observing student activities in STEM-PjBL can be carried out very well. In this way, the STEM-PjBL module that has been developed is suitable for use in physics learning.